GLUCOSE LEVEL ANALYSIS ON STORED PACKED RED CELLS - Melissa Heidy Wongsari; Rachmawati Muhiddin; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
The main source of energy for red cell metabolism is glucose via glycolytic pathway. Red cells metabolism slows down during storage at 2–6OC. Biochemical changes during storage are called storage lesions, i.e. decreased pH, glucose, and ATP, lactic acid accumulation, and loss of red cells function. Samples taken from the tip of PRC bags in CPDA-1 of the same code are divided into four sections, and stored in the blood bank refrigerator at 2–6OC. Glucose level is measured using ABX Pentra 400 (Horiba, Japan) on storage day 3 as a control, day 7, day 14, and day 21. Glucose levels during storage decreased significantly between day 3, and day 7 (p < 0.001), between day 7, and day 14 (p < 0.001), and between day 14, and 21 (p < 0.001). Glucose levels of Packed Red Cells (PRC) decrease during storage. Glycolysis occurs during storage although metabolism slows down.